Conversion of lignocellulose into renewable chemicals by heterogeneous catalysis - Kobayashi, Hirokazu; Ohta, Hidetoshi; Fukuoka, Atsushi (Catalysis science & technology, 2012)
Conversion of lignocellulose into renewable chemicals and fuels has received great attention for building up sustainable societies. However, the utilisation of lignocellulose in the chemical industry has largely been limited to paper manufacturing because of the complicated chemical structure and persistent property of lignocellulose. Heterogeneous catalysis has the potential to selectively convert lignocellulosic biomass into various useful chemicals, and this methodology has rapidly progressed in the last several years. In this perspective article, we outline our recent approaches on the heterogeneous catalysis for this challenging subject with related literatures. Lignocellulose has attracted significant attention as a renewable resource for the production of chemicals and fuels. Solid catalysts selectively convert lignocellulosic biomass to useful chemicals.